Air Pollution and Infant Mortality: Evidence from the Expansion of Natural Gas Infrastructure. (19th February 2016) - Cesur, Resul; Tekin, Erdal; Ulker, Aydogan
Abstract : We examine the impact of widespread adoption of natural gas as a source of fuel on infant mortality in Turkey, using variation across provinces and over time in the intensity of natural gas utilisation. Our estimates indicate that the expansion of natural gas infrastructure has resulted in a significant decrease in the rate of infant mortality. Specifically, a one‐percentage point increase in natural gas intensity – measured by the rate of subscriptions to natural gas services – would cause the infant mortality rate to decrease by 4%, which would translate into approximately 348 infant lives saved in 2011 alone.